2014
DOI: 10.1021/jp505412j
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Extracellular Loop II of κ-Opioid Receptor (196–228) with Opioid Peptide Dynorphin in Membrane Environments as Revealed by Solid State Nuclear Magnetic Resonance, Quartz Crystal Microbalance and Molecular Dynamics Simulation

Abstract: κ-Opioid receptor is a member of the opioid receptor family and selectively interacts with the opioid peptide dynorphin. Extracellular loop II (ECL-II) of the κ-opioid receptor displays an amphiphilic helix in membrane environments and the N-terminal α-helix of dynorphin A(1-17) (hereafter DynA17) is inserted into the membrane with the tilt angle of 21° to the bilayer normal. ECL-II peptides (1-33), corresponding to 196-228 of κ-opioid receptor with [1-(13)C]- or [3-(13)C]-labeled amino acids were incorporated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…The results of MD simulations clearly indicated that the C-terminus of DynA17 interacts with the ECL-II residues in the region between Val10 and Gln14. These results suggest that DynA17 interacts with the ECL-II of the κ-opioid receptor through a hydrophobic and short-lived high-affinity electrostatic interaction in the outer surface of the membrane [77].…”
Section: Membrane-bound κ-Opioid Receptorsmentioning
confidence: 82%
See 4 more Smart Citations
“…The results of MD simulations clearly indicated that the C-terminus of DynA17 interacts with the ECL-II residues in the region between Val10 and Gln14. These results suggest that DynA17 interacts with the ECL-II of the κ-opioid receptor through a hydrophobic and short-lived high-affinity electrostatic interaction in the outer surface of the membrane [77].…”
Section: Membrane-bound κ-Opioid Receptorsmentioning
confidence: 82%
“…Solid-state NMR is particularly well suited for elucidating the dynamics, topology, orientation, and high-resolution structures of peptides in the bilayer environment using model and cell membranes. Peptides analyzed using this approach include venoms (melittin [27,29], bombolitin [54]), antimicrobial peptides (lactoferrampin [55], lactoferricin [56], PGLa [57][58][59], MSI-78 [60][61][62], LL-37 [63], pardaxin [62,64], magainin [65], P5 peptide [66], PG-1 [67], piscidin [68], crown ether containing 14-mer peptide [69,70]), K + channels (Shaker B ball peptide [71]), Neu receptor peptide [72], antibiotic peptides (alamethicin [73][74][75]), opioid peptides (dynorphin [76]), and κ-opioid receptor fragment (ECL-II [77]). In this section, the structure details of some of these peptides are reviewed in detail.…”
Section: Structure Determination Of Membrane-bound Peptidesmentioning
confidence: 99%
See 3 more Smart Citations